Bibliometric Analysis of Journals, Authors and Topics Related to Indonesian Mosque Economics Listed in the Dimensions Database - Fanani, Achmad Zainal; Siregar, Saparuddin (SMART Insight, 2024)
This bibliometric study analyzes the current state of research on the topic of